The influence of simulated exploitation on Patella vulgata populations: protandric sex change is size‐dependent. Issue 2 (9th January 2016) - Borges, Carla D. G.; Hawkins, Stephen J.; Crowe, Tasman P.; Doncaster, C. Patrick
Abstract: Grazing mollusks are used as a food resource worldwide, and limpets are harvested commercially for both local consumption and export in several countries. This study describes a field experiment to assess the effects of simulated human exploitation of limpets Patella vulgata on their population ecology in terms of protandry (age‐related sex change from male to female), growth, recruitment, migration, and density regulation. Limpet populations at two locations in southwest England were artificially exploited by systematic removal of the largest individuals for 18 months in plots assigned to three treatments at each site: no (control), low, and high exploitation. The shell size at sex change ( L 50 : the size at which there is a 50:50 sex ratio) decreased in response to the exploitation treatments, as did the mean shell size of sexual stages. Size‐dependent sex change was indicated by L 50 occurring at smaller sizes in treatments than controls, suggesting an earlier switch to females. Mean shell size of P. vulgata neuters changed little under different levels of exploitation, while males and females both decreased markedly in size with exploitation. No differences were detected in the relative abundances of sexual stages, indicating some compensation for the removal of the bigger individuals via recruitment and sex change as no migratory patterns were detected between treatments. At the end of the experiment, 0–15 mm recruits were more abundant at one of the locations but no differences were detected between treatments. We conclude that sex change in P. vulgata can be induced at smaller sizes by reductions in density of the largest individuals reducing interage class competition. Knowledge of sex‐change adaptation in exploited limpet populations should underpin strategies to counteract population decline and improve rocky shore conservation and resource management. Abstract : The manuscript describes a field experiment to assess the effects of simulated human exploitation of limpets Patella vulgata (model species) on their population ecology in terms of protandry (age‐related sex change from male to female). Indication for size dependence of sex change was that L 50 occurred at smaller sizes in treatments than controls, suggesting an earlier switch in size to females. Mean shell size of P. vulgata neuters changed little under different levels of exploitation, while males and females both decreased markedly in size with exploitation. Even with exploitation, mean sizes of different sexual stages were in accordance with natural populations. No differences were detected in their relative abundances, indicating some compensation for the loss of the bigger individuals such as recruitment and sex change. Sex change in P. vulgata can be induced by reductions in density of largest individuals, and that knowledge should be taken into consideration when defining conservation strategies for other sex‐changing limpets.